2003
DOI: 10.1097/01.sla.0000048453.61168.8f
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Hematologic Benefits of Partial Splenectomy for Congenital Hemolytic Anemias in Children

Abstract: In children with hereditary spherocytosis, a partial splenectomy appears to control hemolysis while retaining splenic function. In children with other congenital hemolytic anemias, a partial splenectomy appears to control symptoms of hypersplenism and splenic sequestration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
81
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(91 citation statements)
references
References 25 publications
8
81
0
2
Order By: Relevance
“…(26,29) Vasilescu et al (24,30) have shown that preservation of the lower pole of the spleen allows a better mobilization of the splenic remnant, and a more accurate assessment of the volume. The length of the splenic remnant ranged between 3.5 and 6 cm, depending on the initial size of the spleen.…”
Section: The Role Of Splenectomy In Hereditary Spherocytosismentioning
confidence: 99%
See 2 more Smart Citations
“…(26,29) Vasilescu et al (24,30) have shown that preservation of the lower pole of the spleen allows a better mobilization of the splenic remnant, and a more accurate assessment of the volume. The length of the splenic remnant ranged between 3.5 and 6 cm, depending on the initial size of the spleen.…”
Section: The Role Of Splenectomy In Hereditary Spherocytosismentioning
confidence: 99%
“…In children less than 5 years old, the risk of overwhelming postsplenectomy sepsis may be increased 60-to 100 fold, compared with that of children without a splenectomy (18) There are also concerns that despite the immunizations against encapsulated bacteria and the postoperative antibiotic prophylaxis, the risk after total splenectomy is never eliminated. (17,19,20) Because of this reason, a number of alternatives to total splenectomy have been considered, including auto-transplantation of the removed spleen and partial splenectomy. (21) The use of partial splenectomy, particularly in pediatric patients, aims to retain splenic immunologic function, while at the same time to decrease the rate of hemolysis.…”
Section: The Role Of Splenectomy In Hereditary Spherocytosismentioning
confidence: 99%
See 1 more Smart Citation
“…Con la finalidad de evitar el riesgo de sepsis, se ha planteado como opción la esplenectomía parcial, en la cual alrededor del 90% del bazo es resecado. 67 Así, se reduce de modo sustancial el grado de destrucción eritrocitaria, lo que permite alcanzar con más facilidad un estado de hemólisis compensada, mientras que se deja tejido esplénico residual para mantener un grado aceptable de capacidad fagocítica. El principal reparo a esta técnica es que el tejido esplénico tiene una gran capacidad de regeneración, por lo que, con el paso de los años, se puede volver a la situación previa a la esplenectomía.…”
Section: Terapia Transfusional De Soporteunclassified
“…Efforts should be made to repair or preserve injured spleens and perform partial splenectomy in selected cases of congenital hemolytic anemias. 97 …”
mentioning
confidence: 99%